(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In today’s fast-paced business landscape, digital transformation has become an imperative for businesses that want to stay competitive and relevant. Digital transformation involves using digital technologies to fundamentally change how businesses operate and deliver value to customers. It includes a wide range of strategies, processes and technologies aimed at improving efficiency, improving customer experience and driving innovation. In this article, we explore some key digital transformation strategies businesses can adopt to successfully navigate the complexities of the digital age.